2018
DOI: 10.1016/j.euroecorev.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimal favoritism in all-pay auctions and lottery contests

Abstract: We analyze the revenue-enhancing potential of favoring specific contestants in complete information all-pay auctions and lottery contests with several heterogeneous contestants. Two instruments of favoritism are considered: Head starts that are added to the bids of specific contestants and multiplicative biases that give idiosyncratic weights to the bids. In the all-pay auction, head starts are more effective than biases while optimally combining both instruments even yields first-best revenue. In the lottery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…In this equilibrium the stronger player bids v 1 and the weaker player remains inactive. Franke, Leininger, and Wasser (2018) extend this result to more than 2 players, and compare the expected aggregate effort between a lottery and an APA. It turns out that multiplicative biases are more effective in lotteries because more participation is induced.…”
Section: Additive and Multiplicative Biasesmentioning
confidence: 82%
“…In this equilibrium the stronger player bids v 1 and the weaker player remains inactive. Franke, Leininger, and Wasser (2018) extend this result to more than 2 players, and compare the expected aggregate effort between a lottery and an APA. It turns out that multiplicative biases are more effective in lotteries because more participation is induced.…”
Section: Additive and Multiplicative Biasesmentioning
confidence: 82%
“…Suppose, as in Franke et al (2013) and Franke et al (2018), that the principal can determine the amount of bias that is afforded the winner of the first contest in contest two. The following proposition determines the optimal level of the bias, and indicates the proportional gain that can be achieved by running an optimal two-contest series rather than a single contest.…”
Section: Discussionmentioning
confidence: 99%
“…7 Note that the winner of contest one gains an advantage in contest two that is associated with the act of winning and not with the margin of victory. A one-shot contest using a form similar to (2) has been investigated by Franke et al (2013) and Franke et al (2018). Beviá and Corchón (2013) investigate a two-player model in which the outcome of the first contest affects contestants' strength in a second contest.…”
Section: Modelmentioning
confidence: 99%
“…3 This class contains the biased lottery or fixed-prize raffle as special case (f i (x i ) = i x i ), but also other types of favoritism like head starts (f i (x i ) = x i + i ), where players obtain an up-front lump-sum bonus of lottery tickets. For simple contest games, this general class of contest success functions has been analyzed in Franke, Leininger, and Wasser (2018), where it is shown that within this class an appropriately biased lottery leads to highest total contributions. In other words, competitive pressure under the optimally biased lottery is higher in comparison to any other contest success function of this class.…”
Section: More General Contest Success Functionsmentioning
confidence: 99%